Ghost in the Genevan borderscape! On the symbolic significance of an "invisible" border. Issue 1 (11th June 2019) - Sohn, Christophe; Scott, James W.
Abstract : This paper explores the symbolic significance of national borders in a cross‐border regional context. The main argument is that the transformation of borders is actually part of a complex and contested process of symbolisation, predicated on articulations between political projects, everyday experience, and collective memories. The Greater Geneva borderscape provides an emblematic case of cross‐border cooperation that is marked by the physical erasure of the Franco‐Swiss border. Rather than an absence of symbolisation, we hypothesise that the border continues to play a symbolic role through its implied "absence" in the affirmation of a cross‐border territorial project. First, we show how the invisibilisation of the border in the Greater Geneva spatial imaginaries is in fact a symbolisation strategy aimed at underlining its obsolete character. Second, we reveal how the discordances between the symbolic recoding of the border by cross‐border cooperation elites and existing popular imaginations and competing meanings weakens the project. To the extent that borders are powerful symbols that are intended to stimulate emotions and a sense of belonging, the ability to mobilise their meaning‐making capacity is at the heart of symbolisation politics, as much for the proponents of open borders and cross‐border cooperation as for the reactionary forces that emphasise national interests and ontological insecurity. Abstract : This paper explores the symbolic significance of national borders in a cross‐border regional context. The main argument is that the transformation of borders is actually part of a complex and contested process of symbolisation, predicated on articulations between political projects, everyday experience, and collective memories. The Greater Geneva borderscape provides an emblematic case of cross‐border cooperation in which the invisibilisation of the border in the spatial imaginaries is in fact a symbolisation strategy aimed at underlining its obsolete character.